Fungal and viral entomopathogens as a combined strategy for the biological control of fall armyworm larvae in maize - Gomez Valderrama, Juliana Andrea; Cuartas Otalora, Paola Emilia; Espinel Correal, Carlos; Barrera Cubillos, Gloria Patricia; Villamizar Rivero, Laura (BMC in United Kingdom, 2023)
Background: The fall armyworm Spodoptera frugiperda is one of the major pests in maize crops, causing important production losses. The pest has rapidly spread worldwide, generating an urgent need to develop efcient and sus‑ tainable strategies for its control. In this work, the potential of integrating nucleopolyhedrovirus- (NPV) and the fungus Metarhizium rileyi to control S. frugiperda larvae was evaluated under laboratory, greenhouse, and feld conditions. Methods: The mortality of S. frugiperda larvae was evaluated after the application of NPV and M. rileyi alone or in combination using three concentrations (high, medium and low) under laboratory conditions. Then, two greenhouse trials using maize plants were carried out to evaluate the efect of individual or combined applications of NPV and M. rileyi on S. frugiperda mortality (frst trial) and fresh damage (second trial). Finally, a trial under feld conditions was conducted to evaluate the performance of the treatment selected in the greenhouse assay. Results: The combined use of NPV: M. rileyi applied simultaneously showed an additive efect in laboratory, causing higher larval mortality than the biocontrol agents used separately. This efect was evident in the mixtures using the concentration levels high:medium, medium:medium, and medium:high. Under greenhouse conditions, the use of a 50:50 ratio of the two entomopathogens also caused higher larval mortality and a signifcantly reduced insect dam‑ age to plants. Finally, under feld conditions, the individual or sequential application of NPV and M. rileyi using 100% of their recommended doses, and the simultaneous application of both entomopathogens at 50% of their recom‑ mended doses, signifcantly reduced the recent foliar damage to levels under the threshold for economic losses (30% fresh damage) while the damage reached 43% when control measures were not used. Conclusion: The combined application of NPV and M. rileyi (two biocontrol agents with diferent mode of action) demonstrated an additive efect that allows to reduce to half their recommended application doses. In this context, the integration of both entomopathogens is a promising strategy to manage S. frugiperda, contributing to improve the economic feasibility of biological control tools for the sustainable fall armyworm management.